2014
DOI: 10.1038/eye.2014.36
|View full text |Cite
|
Sign up to set email alerts
|

Presoaking with BSS used for thin manually dissected DSEK (TMDSEK): a viable option for thin DSEK

Abstract: Aim To describe a novel technique for the safe manual dissection of thin donor lenticules in 10 consecutive patients undergoing DSEK surgery. Methods A key element of our new technique was to presoak the donor cornea in balanced salt solution (BSS) for 30 min before manual dissection. The cornea was placed on an artificial anterior chamber and pressure in the chamber was maintained at 80 mm Hg. The limbus of the donor cornea was incised to the same depth as the central corneal thickness. Lamellar dissection wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…In our practice, we recently reported 10 consecutive cases of thin manual DSEK (TMDSEK) using tissue pre-soaked in balanced salt solution, achieving a mean graft thickness of 90.7 microns (range 48-137 microns) at one month postoperatively. 125 Busin has also reported better visual outcomes with his ultrathin-DSAEK technique compared with conventional DSAEK, achieving grafts of 73+/-14 microns.…”
Section: Reducing Graft Thicknessmentioning
confidence: 99%
“…In our practice, we recently reported 10 consecutive cases of thin manual DSEK (TMDSEK) using tissue pre-soaked in balanced salt solution, achieving a mean graft thickness of 90.7 microns (range 48-137 microns) at one month postoperatively. 125 Busin has also reported better visual outcomes with his ultrathin-DSAEK technique compared with conventional DSAEK, achieving grafts of 73+/-14 microns.…”
Section: Reducing Graft Thicknessmentioning
confidence: 99%
“…The challenges when interpreting long-term data in DSEK is that the technique itself has evolved and we have been able to achieve thinner DSEK grafts more consistently. 4 Mean graft thickness in Wacker's cohort was 155 μm, which may or not be representative depending on the institution and technique employed. 20 Busin et al 11 reported 2-year outcomes following UT-DSAEK (mean graft thickness of 78.28 μm) with mean BSCVA at 24 months of 0.04 LogMar, with 48.8% of patients in the entire cohort achieving a visual acuity of 20/20 or better and suggested that outcomes with UT-DSAEK were comparable to DMEK.…”
Section: Visual Outcomementioning
confidence: 96%
“…10 Although these numbers are improved in the hands of experienced DMEK surgeons, they are still higher than complication rates reported for DSEK, UT-DSEK, TMDSEK, and PDEK. 4,5,[10][11][12] In a comparative study, graft detachment requiring rebubbling occurred in 3.2% of DSAEK cases and 8.6% of DMEK cases. 12 The deleterious effects of rebbubling and additional surgical manipulation on the graft have been established both in vitro and in vivo.…”
Section: Post-operative Complicationsmentioning
confidence: 99%
See 2 more Smart Citations